Resíduo industrial de aveia: extração e caracterização do amido visando aplicação em revestimento comestível adicionado de composto antifúngico natural - Costa, Douglas Rangel da (2018)
Oats (Avena sativa L.) is a cereal that has multiple forms of use and that, along industrial processing, it is observed the generation of residues. The objective of this work was to develop an edible starch-based coating extracted from industrial oat residue with added natural antifungal compound. Samples of oat starch (OS) and residual oat starch (RS) were submitted to the following physicochemical analyzes: moisture, ash, protein, lipids and starch. The edible film was developed by the casting method, using RS, and glycerol as plasticizing agent, and the following properties were determined: thickness, solubility, water vapor permeability and perforation. In parallel, the crude extract (CE) containing antifungal compound produced from the Hansenula wingei culture, and the filmogenic solution elaborated with RS, glycerol and CE (FSCE), were submitted to the antifungal assay in liquid medium, evaluating the inhibitory effect on the spore germination and the mycelial development of Penicillium expansum. The extraction of the starch from the industrial residue of oats presented a satisfactory yield (30.46%), with contents of humidity and purity within the standards established by the legislation. The film developed based on residual oat starch presented a thickness, solubility, water vapor permeability and perforation, satisfactory for use as an edible coating, with perspectives of application in fresh fruits. The antifungal compound was effective against P. expansum, inhibiting spore germination and development of hyphae in 97.74 and 87.92%, respectively. In the experiments carried out on the crude extract (CE) after 90 °C heat treatment for 30 minutes, it was also effective in inhibiting spore germination (64.59%) and mycelial development (84.48%) against the same mould. About the antifungal assay with filmogenic solution, FSCE controlled spore germination (30,52%) and the hyphal growth (61.52%) of P. expansum efficiently and significantly, when compared to the FSwater The results were satisfactory for the use of the starch (OS) in edible coating added of natural antifungal compound, with perspectives of application in fruits in natura. The incorporation of antifungal compound into the film will allow the study of the inhibitory effect of filamentous fungi, associated to the increase in shelf life of fruits destined for direct consumption.